Problems in the treatment of dyshormonal breast hyperplasia: current aspects - E. A. Sukhareva; S. V. Kozlov; A. V. Gailis (Опухоли женской репродуктивной системы, 2014)
Chemoprophylaxis involving the use of pharmacological or natural agents to prevent cancer is a promising line for the secondary preven- tion of breast cancer.Positive results as clinical improvement and attenuated breast epithelial dysplasia were obtained while treating with combined oral con- traceptives in 33.3–90%, with gestagens in 87-90%, with estrogens in 87–92%, with androgens in 64–89%, and with antiestrogens in 82–92% of women with benign dyshormonal diseases.